Systems of seeing: Virtual gaze interaction. Issue 2 (1st December 2018) - Ambrose, Jeremiah
Augmenting Berger's Ways of Seeing (1972), this article seeks to define and contextualize the most dominant form of perceptual interaction in virtual reality. Combining my own practice with an art-historical overview, I explore a creative application of interactive 360° film, whilst also addressing the need to critically engage with this new medium. I propose that given the rate at which metadata became one of the most valuable commodities of the twenty-first century, our ocular interactions will no doubt become subsumed into these systems. As the discourse of digital artistic practice shifts from digital to post-digital a central concern of virtual reality is the disembodiment it generates, but the irony here is that the first-person body is in fact a virtual camera. More in line with Vertov's (1896–1954) prescient cybernetic concepts surrounding the kino-eye, virtual gaze interaction offers utopian real-time interaction in the same breath as it exemplifies an Orwellian nightmare. Beyond this cinematographic perspective of the virtual body is the more pertinent need to explore the implications and potential applications of this new type of interaction. The gaze has been a site of theoretical discussion for many theorists, including; Sartre, Foucault and Virilio. However, the interactive gaze is still a site in need of a discourse. Discussed in this article is a site-specific installation, which physically and virtually demonstrates an application of virtual gaze interaction applied to Magritte's La Clef Des Songes (The Key to Dreams). Extending from Berger's choice in cover art, it uses different forms of reproduction towards a focus not on what is lost, but what is gained through these new processes of visual interaction. In addition to establishing a historiography and associated praxis for virtual gaze interaction, I present a framework for digital futures pertaining to ocular interactions in media art and beyond. Embedded in this discussion are considerations on the politics of vision and the potential impact this will have on how we perceive and the perception of media art.